Social media for selection : are New Zealanders prepared? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts, Master of Arts in Psychology, at Massey University, Manawatū, New Zealand - McPherson, Kirsty (Massey University, 2019)
Personnel selection is a process which most people go through in their life. Job seeking is also a process which most people experience and there are many ways in which people are able to find new jobs as well as information about organisations they want to work for. Social media has a significant impact in many New Zealanders’ daily lives. As people are spending so much of their time online it is commonly believed among recruiters that one’s social media presence can be informative in terms of what people may be like as employees (Berkelaar, 2014; Berkelaar, 2017; Bogen & Rieke, 2018; Doherty, 2010; Jeske & Shultz, 2015; Kashi, Zheng, & Molinaux, 2016). This study aimed to explore New Zealanders’ perceptions of the use of social media as both a job seeking tool and as a selection tool. Through conducting individual interviews and one focus group, a thematic analysis was conducted to explore New Zealanders’ experiences with social media in job seeking and selection. Overall, job seekers found social media a useful tool to find jobs and gather information about organisations they were interested in to curate their CVs and prepare to apply. However, many job seekers had negative perceptions of organisations in terms of organisational justice when social media was used for selection decisions. For recruiters, social media was a useful tool in searching ‘red flags’ in order to cut down candidate lists to the most suitable applicants. The results of this study suggest that job seekers should be aware of the potential for organisations to screen their social media and be prepared for it. For organisations, the results suggest that social media can be a good tool for advertising roles and presenting themselves positively, however they need to take into account the negative impression they may create if using social media during selection.
Keywords: Employee selection; Job hunting; Social media; New Zealand